\(\dfrac{3x-5y}{2}=\dfrac{7y-3z}{3}=\dfrac{5z-7x}{4}=\dfrac{21x-35y}{14}=\dfrac{35y-15z}{15}=\dfrac{15z-21x}{12}\)
Áp dụng tính chất của dãy tỉ số bằng nhau:
\(\dfrac{3x-5y}{2}=\dfrac{7y-3z}{3}=\dfrac{5z-7x}{4}=\dfrac{21x-35y}{14}=\dfrac{35y-15z}{15}=\dfrac{15z-21x}{12}=\dfrac{21x-35y+35y-15z+15z-21x}{14+15+12}=\dfrac{0}{41}=0\)
=>3x-5y=7y-3z=5z-7x=0
3x-5y=0 <=> 3x=5y <=> \(\dfrac{x}{5}=\dfrac{y}{3}\) (1)
7y-3z=0 <=> 7y=3z <=> \(\dfrac{y}{3}=\dfrac{z}{7}\) (2)
Từ (1) và (2) suy ra \(\dfrac{x}{5}=\dfrac{y}{3}=\dfrac{z}{7}\)
Áp dụng tính chất của dãy tỉ số bằng nhau: \(\dfrac{x}{5}=\dfrac{y}{3}=\dfrac{z}{7}=\dfrac{x+y+z}{5+3+7}=\dfrac{17}{15}\)
=>\(x=\dfrac{17}{15}.5=\dfrac{17}{3};y=\dfrac{17}{15}.3=\dfrac{17}{5};z=\dfrac{17}{15}.7=\dfrac{119}{15}\)
Vậy ...........